Pengaruh Gaya Kepemimpinan Transformasional, Budaya Organisasi, Dan Disiplin Kerja Tehadap Kinerja Karyawan PT. Bank XXX - Seftin Khoirun Nisa; Hadi Sunaryo; Fahrurrozi Rahman (E-JRM : Elektronik Jurnal Riset Manajemen, 2022)
Abstract The aims of this study are: 1) To describe transformational leadership style, organizational culture, work discipline and employee performance, 2) To analyze transformational leadership style, organizational culture, work discipline and its influence on employee performance, 3) To analyze the effect of transformational leadership style on employee performance, 4) To analyze the influence of organizational culture on employee performance, 5) To analyze the effect of work discipline on employee performance. This study uses a saturated sample, namely all employees of PT. Bank XXX totaling 57. The results of this study indicate that: 1) Transformational leadership style, organizational culture, work discipline have a significant effect on employee performance, 2) Transformational leadership style has a positive and significant effect on employee performance, 3) Organizational culture has a positive and significant impact on employee performance, 4) Work discipline has a positive and significant effect on employee performance.  Keywords: transformational leadership style, organizational culture, work discipline and employee performance